Radiography doctorates in Arabia: Current position and opportunities to transform research practice in the Middle East. Issue 1 (February 2021) - Elshami, W.; McConnell, J.; Abuzaid, M.; Noorajan, Z.
Abstract: Introduction: Despite the existence of opportunities for postgraduate studies in radiography, the number of radiographers involved in postgraduate education is low and their research production is also considered low compared to other professions. The main aim of this study was to understand the profile of radiography Doctorate holders across the Arab countries, document their current role and identify barriers that may influence research and professional publication activity. Methods: There is no formal database of doctoral radiographers in Arab countries, therefore a snowball sampling technique was used to recruit participants beyond those identified through organizational websites. An online survey was distributed to the participants with implied consent being applied through completion of the survey. Results: From 53 responses, 78% were male and 98% were diagnostic radiographers. Fifty-one percent completed their PhD in non-Arab countries and 55% self-funded (paid for themselves) their PhD study. An increase in doctoral students was observed over time, where 36% (n = 19) of participants will graduate in 2020 and afterward. Barriers reported as preventing radiographers pursuing research/publication were support, employing institutions, lack of research focussed leadership and lack of collaboration. Conclusion: Government support and direction from national professional bodies is needed. To enable research growth, there must be a foundational component within pre-registration/licensing education. Implications for practice: Focussing on government or professional body supported projects that are divided into smaller linked investigations can provide foundational work for PhD development. It is through these opportunities that practitioner research enhancement and capability is improved. Potential Arabian regional and wider international collaborations should be pursued in future as a developmental approach.